Marginal fit of cast titanium copings related to investments and casting techniques (Revista da Faculdade de Odontologia - UPF, 2011)
The purpose of tbis study was to evaluate marginal tit of cast titanium copíngs accordíng to the following conditiotis: 7) three ínvestment types (Rematitan Plus, Rematítan Ultra and Ticoat 5+L Meniredi), 2) use of a "dol!" made up with the thtee ínvestments and the ring filling with conventional phosphate investment; 3) use oi die reiief; 4) sutiece treatment (sandblasting wíth glassbeads, aJuminum oxide, and drilling). Casting was made using appropriate equipment for títanium aFoys (F./.{ijvJanfredi),The results obteined led us.to cone/ude that . it is possíble to obtain titsnium casts with satisfactory marginal fit using adequate techníques; Rematitan ínvestments led to good results, although they may not be used without die reliet, especially when lhe cover techniqueis employed; Ticoat 5+L was the least criticaI regarding casting techníques, but requires dril/ing toobtain good fit.